1997
DOI: 10.1124/mol.52.6.1113
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Sites for Inverse Modulation ofN-Methyl-d-Aspartate Receptors by Sulfated Steroids

Abstract: Steroid sulfation occurs in nervous tissue and endogenous sulfated steroids can act as positive or negative modulators of N-methyl-D-aspartate (NMDA) receptor function. In the current study, structure-activity relationships for sulfated steroids were examined in voltage-clamped chick spinal cord and rat hippocampal neurons in culture and in Xenopus laevis oocytes expressing NR1(100) and NR2A subunits. The ability of pregnenolone sulfate (a positive modulator) and epipregnanolone sulfate (a negative modulator) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(164 citation statements)
references
References 32 publications
5
157
0
1
Order By: Relevance
“…Hence, the nature of or requirement for a charged group at C3 is not clear. However, reduction of the charged residue at C3 results in ablation of activity (Park-Chung et al, 1997). Studies using pregnenolone, in which a hydroxyl group is at C3, have not been reported.…”
Section: Action At Ligand-gated Ion-channel Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the nature of or requirement for a charged group at C3 is not clear. However, reduction of the charged residue at C3 results in ablation of activity (Park-Chung et al, 1997). Studies using pregnenolone, in which a hydroxyl group is at C3, have not been reported.…”
Section: Action At Ligand-gated Ion-channel Receptorsmentioning
confidence: 99%
“…In addition to pregnenolone sulfate activating NMDA receptors, other pregn-5-ene steroids also potentiate NMDA responses (Irwin et al, 1994;Park-Chung et al, 1997). Reduction of the C21 ketone or C17 hydroxylation reduces activity at NMDA receptors, and removal of the C19 side chain to yield dehydroepiandrosterone sulfate reduces activity even further.…”
Section: Action At Ligand-gated Ion-channel Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamate levels are increased in the midbrain of mated and receptive rodents that have elevated midbrain 3α,5α-THP compared with non-receptive rodents (Frye, 2001). Blocking P's metabolism to 3α,5α-THP reduces glutamate's excitatory effects (Park-Chung et al, 1997). Blocking NMDARs in the VTA enhances 3α,5α-THP-facilitated lordosis of rodents (DeBold et al, 2000;Frye and Petralia, 2003c).…”
Section: Progestin-nmda Type Glutamate Receptor (Nmdar) Interactionsmentioning
confidence: 99%
“…Hill, Parizek, Kancheva, et al, 2010;Malayev, Gibbs, & Farb, 2002;Weaver, et al, 2000). On the other hand, the 5ǐ-PIC exert an antagonistic effect on NMDA-r (Malayev, et al, 2002;Park-Chung, et al, 1997;Weaver, et al, 2000) and promote their desensitization (Kussius, Kaur, & Popescu, 2009). Like the levels of other PIC, the levels of conjugated 3Ǐ,5ǐ-THP are also extremely elevated in pregnant women and (in contrast to slightly increasing, stagnating or even decreasing levels of GABAergic PI) pronouncedly rise in the late pregnancy (Gilbert Evans, Ross, Sellers, Purdy, & Romach, 2005; M. Hill, et al, 2007;M.…”
Section: Effects Of 5α/ -Reduced Pregnanes In Pregnant Women and Fetumentioning
confidence: 99%